Fourth grade fairy - Cook, Eileen (New York : Aladdin, 2011)
When fairy-godmother-in-training Willow's wish to attend a human school comes true, she finds getting along with humans to be harder than she expected, but her newly-acquired magical talent makes it easy to collaborate with animals.
K
b
b
Keywords: Fairies -- Fiction; Schools -- Fiction; Human-animal communication -- Fiction; Sisters -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Animals -- Fiction